Prayer Time and Qibla Direction in Near Earth Space - Sulthani, Dinil Abrar (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
Performing prayers is an obligation for Muslims wherever they are. The time and direction of the Qibla where they are located on the surface of the earth can certainly be observed and determined normally using both projections and solar shadows. But an obstacle occurs when a Muslim will pray while he is in outer space near the earth such as on the international space station, or other space stations that exist today or in the future, so studies are needed to get a solution to this condition. Ijtihad ulama expressed several opinions such as using a benchmark time from the last location where the Muslim astronaut departed or using the prayer schedule used in Mecca. While facing the Qibla direction, there are four optional references such as facing the Kaaba on Earth in the relative movement of the spacecraft, following the projection of the Kaaba, facing towards the Earth, and facing in all directions based on belief.